Increasing Knowledge of Biodiversity on the Orphan Seamount: A New Species of Tedania (Tedaniopsis) Dendy, 1924 - Ríos, Pilar; Cristobo, Javier; Baker, Emily; Beazley, Lindsay; Culwick, Timothy; Kenchington, Ellen (Frontiers in Marine Science, 2021)
A new Tedania species (Porifera) was collect using remotely operated vehicles during the Canadian mission HUD2010-029 and the British RRS Discovery Cruise DY081, on the Orphan Seamount near the Orphan Knoll, northwest Atlantic, between 2999.88 and 3450.4 m depth. Orphan Knoll is an isolated, drowned continental fragment 550 km northeast Newfoundland in the Labrador Sea. This region is biologically rich and complex and in 2007, the regional fisheries management organization operating in the area regulated that no vessel shall engage in bottom-contact fishing activities until reviewed in 2020 with a review slated at the end of this year. Members of the genus Tedania are uncommon in the temperate northern hemisphere with only six species known previously: Tedania (Tedania) anhelans; Tedania (Tedania) pilarriosae; Tedania (Tedania) suctoria; Tedania (Tedania) urgorrii; Tedania (Tedaniopsis) gurjanovae; and Tedania (Tedaniopsis) phacellina. The particular features of the new sponge we describe are the very peculiar external morphology which is tree-like with dichotomous branching—a morphology not previously described in this subgenus; and the combination of spicules found: long styles, the typical tornotes of the subgenus and two sizes of onychaetes. Additional information is provided on other species of Tedaniopsis described from the Atlantic Ocean. Based on the characteristics reported, we propose a new species, Tedania (Tedaniopsis) rappi sp. nov. in honor of Prof. Hans Tore Rapp (1972–2020), University of Bergen, Norway, a renowned sponge taxonomist and coordinator of the Horizon 2020 SponGES project. The holotype of T. (T.) phacellinaTopsent, 1912 from the Azores, the only other northern Atlantic species in the subgenus Tedaniopsis, was reviewed for comparison.